ChemInform Abstract: Efficient Chromium(II)‐Catalyzed Cross‐Coupling Reactions Between Csp2 Centers. Issue 11 (18th March 2014) - Steib, Andreas K.; Kuzmina, Olesya M.; Fernandez, Sarah; Flubacher, Dietmar; Knochel, Paul
Abstract Various (hetero)arylmagnesium reagents (some of them as LiCl adducts) are coupled with N‐heterocyclic halides, aromatic halogenated ketones or imines, and alkenyl iodides.